Influence of Medium Components and Physical Factors on Vitamin B Production by Pseudomonas sp. PCSIR 99 (Biological Sciences - PJSIR, 2007)
Study  of  the  i nfl uence  of  var ious  carbon  sources  on  prod uction  of  vitami n  8  by  Pseudomonas  sp. PCSTR 99 showed that methanol, meth ylami ne and I , 2-propanediol promoted vitam i n 8 production when grown on the modi fi ed basal m ed i um emended w ith 0.2% 5, 6-dimethyl ben zi mid azole. Amon g the nitrogen sources tested , L-aspartate   and   L-meth ion i ne  enhanced   vi tami n   8    production   and  cell  mass dramatical l y.  Any   upward   or down121 2 ward  change  i n  pH  from  6.5  and  i n  temperature  from  32  °C  decreased  the  l evel  of  vi tami n  8    i n  the  m ed i um.Whereas,   I  0%  oxygen  and  0.004  mM  cobalt  ion  concentration   i ncreased  vitami n  8    prod uction  si gnificantl y.  f t  i s12ferred   th at  v itamin  8   prod u ction  can  also  be  regulated  by  proper   mani pu l ation  of  ph ysical  parameters  of  the m ed i u m as wel l.